2015
DOI: 10.1890/14-1368.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plant, soil, and microbes in a typical steppe from simulated grazing: explaining potential change in soil C

Abstract: Grazing can directly or indirectly influence carbon (C) inputs, turnover, and retention in grassland soil. However, relative to the plant response to grazing, belowground biota and process responses are more complex and often do not correlate with the aboveground responses. Ungulate grazing involves three mechanisms; defoliation (removal of plant shoot tissue), dung and urine return, and trampling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
103
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(118 citation statements)
references
References 80 publications
(147 reference statements)
5
103
0
3
Order By: Relevance
“…Grazing may directly affect soil microbes through altering resource availability such as soil TC and TN, soil moisture, and pH. One direct effect of grazing is through production of dung and urine (Liu et al, ; McNaughton et al, ). Our study showed that the relative abundance of Bacteroidia , an obligate anaerobic gut microbe in animals (Eckburg, ; Winter & Bäumler, ), was higher in WG, likely due to accumulation of dung and urine by intensive grazing in WG (Barik & Murugan, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Grazing may directly affect soil microbes through altering resource availability such as soil TC and TN, soil moisture, and pH. One direct effect of grazing is through production of dung and urine (Liu et al, ; McNaughton et al, ). Our study showed that the relative abundance of Bacteroidia , an obligate anaerobic gut microbe in animals (Eckburg, ; Winter & Bäumler, ), was higher in WG, likely due to accumulation of dung and urine by intensive grazing in WG (Barik & Murugan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Grazing with large herbivores is a common land use strategy for livestock production as well as maintaining plant species diversity and ecosystem functioning (Bardgett & Wardle, ; Koerner & Collins, ; Liu, Kan, Yang, & Zhang, ). Many previous studies focus on grazing impacts on plant productivity, community composition, and allocation of carbon (C) and nitrogen (N) between aboveground and belowground parts (Dong et al, ; Doust, ; Kotzé, Sandhage‐Hofmann, Amelung, Oomen, & du Preez, ; McNaughton, Banyikwa, & McNaughton, ; Zechmeister, Schmitzberger, Steurer, Peterseil, & Wrbka, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A coupled climate‐carbon cycle model predicted an accelerated loss of soil organic carbon to the atmosphere if the warming continues on the plateau [ Zhuang et al , ]. In addition to climate changes, the shift of land use pattern can directly or indirectly influence carbon inputs, turnover, and retention in the grassland soil on the plateau [ Liu et al , ]. For example, the enhancing grazing may have substantially increased the respiration rate of the alpine meadow soil, which releases 1530–2040 g CO 2 to the atmosphere annually [ Cao et al , ], much higher than that of the natural alpine meadow soil [ Bosch et al , ].…”
Section: Introductionmentioning
confidence: 99%